Impact of Circuit Training on Cardiovascular Adaptation: A 10-Week Intervention Study on Sedentary Students at Ignatius Ajuru University of Education, Port Harcourt, Nigeria - Gonsi, Monday Sibe; Ofurum, Chukwudi (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
Sedentary behavior among university students poses significant cardiovascular health risks, yet evidence for effective interventions remains limited. This quasi-experimental study evaluated the cardiovascular adaptations following a structured 10-week circuit training intervention on sedentary students, Ignatius Ajuru University of Education Port Harcourt, Nigeria. Sixty participants (mean age: 21.4 ± 2.3 years; 55% male; mean BMI: 22.9 ± 2.6 kg/m²) were randomly assigned to experimental (n=30) and control (n=30) groups using computer-generated numbers. The intervention consisted of three weekly supervised sessions with 8-12 exercise stations, a 30:15 work-to-rest ratio, and 65-85% maximum heart rate. Main outcome measures included cardiorespiratory endurance through the 20-meter multistage fitness test, heart rate recovery, and resting heart rate. Secondary measures were blood pressure and exercise tolerance. Analysis of Covariance revealed significant improvements in the experimental group's CRE (pre: 37.28 ± 7.57, post: 41.61 ± 7.39 ml/kg/min; mean difference: 4.32 ml/kg/min; p=.007, η²=.126) compared to controls (pre: 37.11 ± 4.39, post: 37.35 ± 4.56 ml/kg/min; mean difference: 0.23 ml/kg/min). The experimental group also presented with significant improvements in resting heart rate (-6.2 bpm), blood pressure (-6/-3 mmHg), and exercise tolerance (+3.3 minutes), whereas the control group presented with minimal changes. These findings suggest that structured circuit training is an effective method of improving cardiovascular adaptation in sedentary university students and offer a time-efficient intervention strategy for the improvement of cardiovascular health in this at-risk population.